2014
DOI: 10.1002/app.40938
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating effects of biobased 2,5‐furandicarboxylate esters as plasticizers on the thermal and mechanical properties of poly (vinyl chloride)

Abstract: We synthesized 2,5‐furandicarboxylate esters [i.e., dibutylfuran‐2,5‐dicarboxylate, diisoamylfuran‐2,5‐dicarboxylate, and di(2‐ethylhexyl)furan‐2,5‐dicarboxylate] and investigated their potential application as plasticizers of commercial poly(vinyl chloride) (PVC) products. Fourier transform infrared analysis, mechanical tests, scanning electron microscopy investigation, differential scanning calorimetry analysis, dynamic mechanical thermal analysis, thermogravimetric analysis (TGA), melt flow rate (MFR) measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 55 publications
(61 reference statements)
6
32
0
Order By: Relevance
“…Step 3 The results showed that all the plasticized PVC blends underwent three stages of degradation, and this was in agreement with earlier observations reported in the literature [2,21,23,34,35]. In the first stage of degradation, the weight loss was due to plasticizer evaporation.…”
Section: Weight Loss (%)supporting
confidence: 89%
“…Step 3 The results showed that all the plasticized PVC blends underwent three stages of degradation, and this was in agreement with earlier observations reported in the literature [2,21,23,34,35]. In the first stage of degradation, the weight loss was due to plasticizer evaporation.…”
Section: Weight Loss (%)supporting
confidence: 89%
“…This influence on the morphology of plasticized mixtures (with ISB, ATBC, ESO and ESOME) can be attributed to a decrease in the matrix viscosity and denotes a good dispersion of plasticizers in the PVC matrix [35] .…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…Additionally worth considering are esters of furan dicarboxylic acid (FDCA), since some of these are effective PVC plasticizers and the precursor acid can be derived from agricultural residues . In the present work, three different dialkyl furan‐2,5‐dicarboxylates (also referred to as furan dicarboxylic acid esters, FDAE) were utilized for modification of PVC, of which the following two were novel plasticizers: Diisotridecyl 2,5‐furandicarboxylate; and Mixed 2,5‐furandicarboxylate (having 50% 2‐ethylhexyl, 25% octyl, and 25% decyl substituents).…”
Section: Introductionmentioning
confidence: 99%